2021
DOI: 10.2106/jbjs.cc.20.00821
|View full text |Cite
|
Sign up to set email alerts
|

Macrodystrophia Lipomatosa of Thoracic Spine Causing Progressive Neurodeficit

Abstract: Case: We report the first case of a 21-year-old male patient with macrodystrophia lipomatosa (MDL), with local gigantism involving the thoracic spine and progressively worsening neurodeficit. Imaging studies revealed fatty infiltration and hypertrophied intercostal nerves, dextroscoliosis, osseous hypertrophy between C4 and T2, and severe canal stenosis at the T4 to T5 level secondary to lamino-facetal hypertrophy. He underwent debulking of the lesion and posterior instrumented decompression in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…17 As summarized in our recent review of the world's literature (and updated for this review), we have identified 153 cases of MDL (i.e., reported using this term): 79 cases with documented LN and 74 cases that do not comment on nerve abnormality. 1,2,13,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Overgrowth was most commonly reported with LN of the median nerve at the wrist, followed by plantar nerves. The cases that did not comment on nerve involvement, however, lacked of the site of the suspected lesion, yet alone imaging proximally to the lesion.…”
Section: Observationsmentioning
confidence: 99%
“…17 As summarized in our recent review of the world's literature (and updated for this review), we have identified 153 cases of MDL (i.e., reported using this term): 79 cases with documented LN and 74 cases that do not comment on nerve abnormality. 1,2,13,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Overgrowth was most commonly reported with LN of the median nerve at the wrist, followed by plantar nerves. The cases that did not comment on nerve involvement, however, lacked of the site of the suspected lesion, yet alone imaging proximally to the lesion.…”
Section: Observationsmentioning
confidence: 99%